OP0205 LIVE ATTENUATED VACCINES IN PEDIATRIC RHEUMATIC DISEASES ARE SAFE: MULTICENTER, RETROSPECTIVE DATA COLLECTION. (June 2019) - Uziel, Yosef; Bergonzo, Veronica Moshe; Onozo, Beata; Kulcsar, Andrea; Tróbert-Sipos, Diana; Akikusa, Jonathan; Pileggi, Gecilmara Salviato; Maritsi, Despoina; Kasapcopur, Ozgur; Smerla, Roubini; Rigante, Donato; Atasali, Erato; et al.
Abstract : Background: Common practice is to withhold vaccination with live-attenuated vaccines in patients with rheumatic diseases on high-dose DMARDs, glucocorticosteroids or biological agents, due to limited safety data, and the (theoretical) risk of introducing an infectious disease to the patient. Evidence for this approach is low. We collected data from pediatric rheumatologists who vaccinate these patients, to obtain additional safety data, which might update and revise this approach. Objectives: To collect retrospective data in patients with JIA and other diseases who received live booster MMR or MMRV while on DMARDs, glucocorticosteroids or biological agents. Methods: Data from 13 pediatric rheumatology centers in 10 countries were collected. Results: 234 patients were reported; mean age 5± 2.7, 70% girls. 206 had JIA;. 46% oligoarticular, 36% polyarticular, 8% systemic, 5% SPA types, 5% JIA and uveitis. 48% of JIA patients were in remission on medication. Disease activity was low in 38%, high in 2%, moderate in 7%; 11 patients had juvenile dermatomyositis, 3 systemic and 2 localized scleroderma, 4 isolated idiopathic uveitis, 1 CINCA syndrome, 1 MKD, and 1 FMF. 110 patients had MMR/V booster while on MTX; 3 reported mild side-effects of local skin reaction and pain, none had disease flare. 76 had booster while on MTX+ anti-TNF; 7 reported mild and transient adverse events of local skin reaction, fever and URTI. 39 had booster while on anti-TNF alone; 1 reported fever. 3 had booster while on tocilizumab, 7 on anakinra, and 5 on canakinumab. There was no relation between disease activity, type or duration, sex, age and outcome of vaccinations. No vaccine infection related to measles, rubella, mumps and varicella were reported. Conclusion: This large, retrospective data collection demonstrates that live-attenuated booster vaccine is probably safe in children with rheumatic diseases, on immunosuppressive therapies. This strengthens the new PRES recommendation: "Vaccination of live-attenuated vaccines in patients on high-dose DMARD, high-dose glucocorticosteroids or biological agents can be considered on a case-by-case basis, weighing the risk of infections against the hypothetical risk of inducing infection through vaccination." These data provide the basis for a large, prospective data collection study that is planned by the PReS vaccination study group. It will increase the current level of evidence for the safety of vaccinations in our pediatric rheumatology population. Disclosure of Interests: Yosef Uziel: None declared, Veronica Moshe Bergonzo: None declared, Beata Onozo: None declared, Andrea Kulcsar: None declared, Diana Tróbert-Sipos : None declared, Jonathan Akikusa: None declared, Gecilmara Salviato Pileggi : None declared, Despoina Maritsi: None declared, Ozgur KASAPCOPUR: None declared, Roubini Smerla: None declared, Donato Rigante: None declared, Erato Atasali: None declared, Mariana Rodrigues: None declared, Balahan Makay Speakers bureau: Enzyvant, Novartis, Roche, Abbvie, Nico Wulffraat: None declared, Natasa Toplak: None declared